Radical oxidation of methyl vinyl ketone and methacrolein in aqueous droplets: Characterization of organosulfates and atmospheric implications. (January 2019) - Wach, Paulina; Spólnik, Grzegorz; Rudziński, Krzysztof J.; Skotak, Krzysztof; Claeys, Magda; Danikiewicz, Witold; Szmigielski, Rafał
Abstract: In-cloud processing of volatile organic compounds is one of the significant routes leading to secondary organic aerosol (SOA) in the lower troposphere. In this study, we demonstrate that two atmospherically relevant α, β-unsaturated carbonyls, i.e., but-3-en-2-on (methyl vinyl ketone, MVK) and 2-methylopropenal (methacrolein, MACR), undergo sulfate radical-induced transformations in dilute aqueous systems under photochemical conditions to form organosulfates previously identified in ambient aerosols and SOA generated in smog chambers. The photooxidation was performed under sun irradiation in unbuffered aqueous solutions containing carbonyl precursors at a concentration of 0.2 mmol and peroxydisulfate as a source of sulfate radicals (SO4 – ) at a concentration of 0.95 mmol. UV–vis analysis of solutions showed the fast decay of unsaturated carbonyl precursors in the presence of sulfate radicals. The observation confirms the capacity of sulfate radicals to transform the organic compounds into SOA components in atmospheric waters. Detailed interpretation of high-resolution negative ion electrospray ionization tandem mass spectra allowed to assign molecular structures to multiple aqueous organosulfate products, including an abundant isoprene-derived organosulfate C4 H8 SO7 detected at m/z 199. The results highlight the solar aqueous-phase reactions as a potentially significant route for biogenic SOA production in clouds at locations where isoprene oxidation occurs. A recent modelling study suggests that such processes could likely contribute to 20–30 Tg year −1 production of SOA, referred to as aqSOA, which is a non-negligible addition to the still underestimated budget of atmospheric aerosol. Graphical abstract: Image Highlights: Methacrolein and methyl vinyl ketone form SOA in atmospheric waters. This proceeds through SO4 radical-mediated reactions to form organosulfates. Structures of organosulfates formed were elucidated and in some cases revised. An abundant isoprene-related organosulfate C4 H8 SO7 ( m/z 199) was detected. Sunlight enhances the oxidative capacity of atmospheric waters.